Исследование трибологических свойств материалов, полученных с помощью плазменной технологии термического напыления для активного зуба - Руснак, Юрый; Каднар, Милан; Ткач, Зденко (НТУ "ХПИ", 2016)
Описана возможность использования материалов таких, как чистый NP55 и смеси NP 20 и NP 40 с материалом CuSnlO, нанесенных на поверхности скольжения и активную сторону зуба с помощью технологии плазменного термического напыления. Результаты эксперимента подтвердили пригодность всех исследуемых материалов и указанной технологии для применения на поверхности скольжения и активной стороне зуба.

This article describes the use of certain types of materials, which are applied to the sliding surface and the active surface of tooth. Applied technology of plasma thermal spraying on the surface of the working parts. The basis of the article is carried out the experiment with the processing of the results. Their assessment gives a complete overview of the main tribological properties of the materials and possible use in the slip node. The first test material it is pure NP55, and die second pair are a mixture of NP 20 and NP 40 with the material CuSnlO. The experimental results confirmed the possibility of using all of the materials using the plasma thermal spraying technology to create a slip node and improve parameters die active surface of the tooth.
Research the tribological properties of the materials obtained by the plasma thermal spraying technology for active tooth
Keywords: экология; трение; смазка; износ; ecology; friction; grease; wear